An Aloe-Based Composition Constituting Polysaccharides and Polyphenols Protected Mice against D-Galactose-Induced Immunosenescence - Mesfin Yimam; Teresa Horm; Alexandria O’Neal; Ping Jiao; Mei Hong; Qi Jia (Journal of Immunology Research)
A decline in immune response, exhibited in the form of immunosenescence and inflammaging, is an age-associated disturbance of the immune system known to predispose the elderly to a greater susceptibility to infection and poor vaccine response. Polysaccharides and polyphenols from botanicals are known for their immune modulation effects. Here we evaluated a standardized mushroom-based composition, UP360, from Aloe barbadensis, Poria cocos, and Rosmarinus officinalis, as a natural nutritional supplement for a balanced immune response in an accelerated aging mouse model. Immunosenescence was induced by continual subcutaneous injection of D-galactose (D-gal) at a dose of 500 mg/kg/day to CD-1 mice. UP360 was administered at oral doses of 200 and 400 mg/kg to the mice starting on the 5th week of D-gal injection. The study lasted for a total of 9 weeks. All mice were given a quadrivalent influenza vaccine at 3 µg/animal via intramuscular injection 14 days before the end of the study. A group of D-gal-treated mice treated at 400 mg/kg/day UP360 was kept without vaccination. Whole blood, serum, spleen homogenate, and thymus tissues were used for analysis. UP360 was found to improve the immune response as evidenced by stimulation of innate and adaptive immune responses, increase antioxidant capacity as reflected by augmented SOD and Nrf2, and preserve vital immune organs, such as the thymus, from aging-associated damage. The findings depicted in this report show the effect of the composition in activating and maintaining homeostasis of the immune system both during active infections and as a preventive measure to help prime the immune system. These data warrant further clinical study to explore the potential application of the mushroom-based composition as an adjunct nutritional supplement for a balanced immune response.